MODEL PENGEMBANGAN KOMPETENSI MANAJERIAL KEPALA SEKOLAH BERBASIS ISLAMIC LEADERSHIP - Oman Fathurohman; Aisyah Aisyah (Universitas Islam Bunga Bangsa Cirebon, 2024)
Background Managerial competence of school principals in Islamic educational institutions is often underdeveloped due to the absence of a systematically grounded development model that integrates Islamic leadership values with contemporary management science. Objective This study aims to construct a conceptual model of managerial competence development for school principals based on Islamic leadership principles and to identify strategic dimensions that support its implementation in Islamic educational institutions. Methodology Library research methodology was employed, utilizing reputable academic books and internationally indexed journal articles published within the last five years. Data collection was conducted through systematic documentation, followed by content analysis and referential adequacy verification for data validity. Results Findings establish a five-component Islamic leadership-based model encompassing visionary, ethical, communicative, strategic, and adaptive managerial competencies, each grounded in Quranic and Hadith principles.